Quality assessment of bottled water from selected water refilling stations in Iloilo City - Diaz , Leolean Nyle de Leon. (2001.)
The quality of three bottled drinking water samples from selected water refilling stations in Iloilo City was evaluated.
Sotech thesis.
Keywords: Bottled drinking water